Trinity Cathedral, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Image depicts a view of the Trinity Cathedral as viewed from inside Woodford Square facing south. The building's facade is partially obscured by trees from inside the square.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Church buildings; Buildings; Catholics